Understanding How Sensory and Digital Marketing Influence Visitors’ Emotional Attachment: A Case Study of Doudo Educational Tourism Village - Faiqoh, Ambar Mahaarotul; Augustinah, Fedianty; Listyawati, Liling (PT. Riset Press International, 2025)
This study aims to analyze the influence of sensory marketing and digital marketing on visitors' emotional attachment at Doudo Educational Tourism Village. Sensory marketing refers to strategies that activate various senses to enhance the consumer experience. In contrast, digital marketing includes using digital platforms to promote products through Doudo Educational Tourism Village tour packages. Visitors' emotional attachment is essential to their satisfaction and loyalty to tourist destinations. The method used in this research is a quantitative approach with a survey as a data collection tool. The respondents of this study were visitors to Doudo Educational Tourism Village, who were taken using a purposive sampling technique. The collected data were analyzed using multiple linear regression techniques to test the relationship between sensory marketing, digital marketing, and emotional attachment variables. The research results show that these two variables, sensory marketing, and digital marketing, significantly influence visitors' emotional attachment. Sensory marketing strongly impacts visitors' feelings towards tourist villages, while digital marketing contributes to creating awareness and strengthening emotional attachment through social media and websites. This research indicates that combining sensory and digital marketing can enhance visitors' experience, strengthen their emotional attachment, and increase their loyalty to Doudo Educational Tourism Village.